Dietary supplement enriched in antioxidants and omega-3 protects from progressive light-induced retinal degeneration. - Khaoula Ramchani-Ben Othman; Christine Cercy; Mohamed Amri; Michel Doly; Isabelle Ranchon-Cole (PLoS ONE, 2015)
In the present study, we have evaluated one of the dietary supplements enriched with antioxidants and fish oil used in clinical care for patient with age-related macular degeneration. Rats were orally fed by a gastric canula daily with 0.2 ml of water or dietary supplement until they were sacrificed. After one week of treatment, animals were either sacrificed for lipid analysis in plasma and retina, or used for evaluation of rod-response recovery by electroretinography (ERG) followed by their sacrifice to measure rhodopsin content, or used for progressive light-induced retinal degeneration (PLIRD). For PLIRD, animals were transferred to bright cyclic light for one week. Retinal damage was quantified by ERG, histology and detection of apoptotic nuclei. Animals kept in dim-cyclic-light were processed in parallel. PLIRD induced a thinning of the outer nuclear layer and a reduction of the b-wave amplitude of the ERG in the water group. Retinal structure and function were preserved in supplemented animals. Supplement induced a significant increase in omega-3 fatty acids in plasma by 168% for eicosapentaenoic acid (EPA), 142% for docosapentaenoic acid (DPA) and 19% for docosahexaenoic acid (DHA) and a decrease in the omega-6 fatty acids, DPA by 28%. In the retina, supplement induced significant reduction of linolenic acid by 67% and an increase in EPA and DPA by 80% and 72%, respectively, associated with significant decrease in omega-6 DPA by 42%. Supplement did not affect rhodopsin content or rod-response recovery. The present data indicate that supplement rapidly modified the fatty acid content and induced an accumulation of EPA in the retina without affecting rhodopsin content or recovery. In addition, it protected the retina from oxidative stress induced by light. Therefore, this supplement might be beneficial to slow down progression of certain retinal degeneration.